PILLARS OF EDUCATION: A WAY TO PREVENT BULLYING IN PHYSICAL EDUCATION'S CLASSES (Fiep Bulletin - online, 2011)
The Pillars of Education have been proposed to attend the education of human development. The Bullying, a form of violence manifested in school is increasing nowadays. Physical Education were interviewed for reporting on Bullying in the classroom in EFE. It was concluded that is present and that the actions are not from the contents of the EF. It was then proposed a list of the Pillars of Education with the content in order to prevent bullying.